Eksistensi Ondofolo dalam Dinamika Pemerintahan Formal Kampung Yobeh - Sanggenafa, Christine O. I.; de Fretes , Diego Romario; Idris, Usman (Universitas Cenderawasih, 2023)
The research, located in Yobeh Village, Jayapura Regency, aims to identify the existence of Ondoafi in the dynamics of informal government in Yobeh Village, Jayapura Regency. This research uses descriptive qualitative method. Data collection is conducted by interview, literature study, and documentation as a complement. The data analysis technique uses data reduction, data display, and conclusion drawing/verification models. This research uses the concept of local strongman. The result of the research shows that community awareness and the existence of Ondofolo determine whether Ondofolo is valued, respected or there has been a change in viewing Ondofolo's leadership. The existence of Ondofolo of Yobe Village is still maintained through the recognition of Ondofolo's position and the recognition of Ondofolo as a customary leader by his followers or community. On the way, disorganisation of Ondofolo khose of Yobe village also occurs as a result of incoming social change, which causes changes due to external factors and internal factors, which become obstacles to the existence of Ondofolo.